A Contemporary Analysis of Kant’s Concept of Goodwill and the Categorical Imperative - Edward Uzoma Ezedike (PINISI Discretion Review, 2020)
This paper makes a contemporary appraisal of the concepts of the ‘Goodwill’ and the ‘Categorical Imperative’ in Kant’s formalistic, deontological ethics. Kant posits that the rightness of an act does not depend at all on the value of its consequences. For him, in order to know whether an act is right or wrong, we need only see whether it is in accordance with a valid moral rule. The test for a valid moral rule, as he conceives it, is purely formalistic.  For a moral rule to be valid, it must pass the test of the foundational, supreme principle or ultimate criterion of morality, which Kant calls the “Categorical Imperative”. On this score, the paper, seeks to address the problem of ethical formalism and foundationalism associated with Kant’s theory in view of the contemporary challenge of ethical pluralism and destructive postmodernism. The objective of the paper is to reconcile with Kantianism with the contemporary shift from moral foundationalism and universalism to anti-foundationalism and relativism.